Methodological foundations of sociological modeling of behaviour of social actors in the context of Max Weber theory - Kabiak, Aleh V. (Journal of the Belarusian State University. Sociology, 2019)
Permissive conditions of sociological modeling are formulated in the context of Max Weber’s interpretive sociology: 1) the ability to consider the thinking of the individual as an internal behaviour; 2) the ability to compare different constellations of motives of behaviour of social actors; 3) the ability to construct ideal types of relations between social actors in the course of sociological analysis; 4) the ability to predict the behaviour of social actors on the basis of subjectively assumed meanings and correlation with the behaviour of other people. A small number of subjects representing the general totality of the modeling object, insufficient knowledge of this object, as well as the non-extensibility of the principle of unambiguous determination on the behaviour of social subjects are considered as limitations of the process of sociological modeling. Sociological modeling of behaviour of social actors allows, first, to determine the dominant motive of motivation, and second, to estimate the measure of the sensitivity of behaviour to external factors, third, to characterize and to quantify (from 0 to 1 or from 0 to 100 %) a measure of consistency in the behaviour of interacting social actors. The basic axiom defining a vector of development of sociological modeling is following: from equiprobable unknown heterogeneity to highly probable understandable certainty.